Co-pyrolysis of biomass and binary single-use plastics: synergy, kinetics, and thermodynamics - Sabah Mariyam; Prakash Parthasarathy; Snigdhendubala Pradhan; Tareq Al-Ansari; Gordon McKay (International Journal of Sustainable Energy, 2023)
Waste management is an increasing global concern due to the rise in urbanization and industrialization. This study examines the co-pyrolysis of date pits (DP) and single-use plastics (polypropylene-PP and Styrofoam-PS) as a way to create value-added products. Single, binary, and ternary mixtures were pyrolyzed at three different heating rates to understand the synergy, kinetics, and thermodynamics. The results showed positive synergy and reduced activation energies during co-pyrolysis, due to varying reaction mechanisms. The positive values of ∆H, ∆G, and negative ΔS indicate endothermic non-spontaneous reactions and disorder in the products instead of the reactants during pyrolysis. Future studies should explore upscaling this process for sustainable energy production.